2016
DOI: 10.1002/2016ja022913
|View full text |Cite
|
Sign up to set email alerts
|

Source region and growth analysis of narrowband Z‐mode emission at Saturn

Abstract: Intense Z‐mode emission is observed in the lower density region near the inner edge of the Enceladus torus at Saturn, where these waves may resonate with MeV electrons. The source mechanism of this emission, which is narrow‐banded and most intense near 5 kHz, is not well understood. We survey the Cassini Radio and Plasma Wave Science data to isolate several probable source regions near the inner edge of the Enceladus density torus. Electron phase space distributions are obtained from the Cassini Electron Spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…A case study of Z-mode waves at Saturn 16 assumed that the direction of wave propagation with respect to the magnetic field (known as the wave normal angle (WNA)) was highly oblique. However, Z-mode waves can also propagate along the magnetic field direction 17,18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A case study of Z-mode waves at Saturn 16 assumed that the direction of wave propagation with respect to the magnetic field (known as the wave normal angle (WNA)) was highly oblique. However, Z-mode waves can also propagate along the magnetic field direction 17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…1b shows that there is a mixture of strong and weak left-hand circular polarization with components of linear polarization (not shown) indicating that there is a distribution of WNAs which includes parallel propagation. Instability analysis shows that Z-mode waves can be generated in the field-aligned direction by an unstable distribution of electrons 17,18 . An analysis of the polarization data for this case shows that the WNAs are mostly close to the magnetic field with a peak at ~22° (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At L < 4 R S in Saturn's magnetosphere, Woodfield et al (2019) proposed that the acceleration of electrons to relativistic energies by whistler waves may lead to the butterfly PADs observed at L ∼ 3 R S (Paranicas, Mitchell, Krimigis, et al, 2010). It has also been shown that there are intense Z-mode waves in this area (Menietti et al, 2015(Menietti et al, , 2016Ye et al, 2010). The intensity of Z-mode waves gradually increase toward smaller L-shells, which may fit to the increasing α eq range of near-equatorial depletion presented in Figure 3.…”
Section: Adiabatic Acceleration By Radial Transport Versus Local Accelerationmentioning
confidence: 99%
“…Recently, Menietti et al (2016Menietti et al ( , 2019 studied the generation mechanism of Z mode emissions for both 5 and 20 kHz and the relation of upper hybrid resonance with NB emissions by analyzing the growth rates of the waves based on the electron phase space distribution measured by the Cassini Plasma Spectrometer (CAPS) Electron Spectrometer (ELS; Young et al 2004). Case studies show the wave normal angel of the Z mode to be usually smaller than 30° (Menietti et al 2018a(Menietti et al , 2018b, and DF results show two possible source regions: one at high latitude on the same magnetic field lines as SKR and another one at the equatorial region interior to the plasma torus (Menietti et al 2018b).…”
Section: Introductionmentioning
confidence: 99%